COVID-19 concomitant with infective endocarditis: A case report and review of management. (September 2020) - Amir, Muzakkir; Djaharuddin, Irawaty; Sudharsono, Albert; Ramadany, Sri
Highlights: Coronavirus disease 2019 (COVID-19) may be present with non-specific clinical manifestations, especially in patients with comorbidities. We present a case of infective endocarditis concomitant COVID-19, illustrating the management and main outcomes in a developing country. Diagnosing and managing a patient with COVID-19 could be challenging, there is not yet an approved medication regimen for COVID-19 infections We present a case of infective endocarditis concomitant COVID-19, illustrating the management and main outcomes in a developing country. Abstract: Coronavirus disease 2019 (COVID-19) has emerged as a pandemic and public health crisis across the world. With its high infectivity and rapid spread, the severity of the disease is escalating in certain populations, especially in patients with pre-existing cardiovascular disease. In developing countries, infective endocarditis remains a problem in patients with rheumatic heart disease. We report the case of a patient with a diagnosis of infective endocarditis concomitant with COVID-19, including the diagnosis, management, and main outcomes.